2021
DOI: 10.3390/vaccines9111332
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Adherence to COVID-19 Vaccination and Serum Antibody Concentration among Hospital Workers—The Experience of an Italian Private Hospital

Abstract: SARS-CoV-2 transmission has been high, especially among healthcare workers worldwide during the first wave. Vaccination is recognized as the most effective approach to combat the pandemic, but hesitation to get vaccinated represents an obstacle. Another important issue is the duration of protection after administration of the full vaccination cycle. Based on these premises, we conducted a study to evaluate vaccination adherence and the anti-S antibodies levels among hospital workers, from January to March, 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…A total of 57 studies, including additional papers found through a reference scanning (n = 3) and a Google search (n = 1), were screened for full-text review. Forty-four studies were eventually considered appropriate [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ] for this literature review, as detailed in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 57 studies, including additional papers found through a reference scanning (n = 3) and a Google search (n = 1), were screened for full-text review. Forty-four studies were eventually considered appropriate [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ] for this literature review, as detailed in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The studies were carried out in 12 out of the 20 Italian regions, with the highest number of studied performed in Lazio (n = 10) followed by Lombardy and Veneto (n = 8) and Campania (n = 6). One study only considered private hospitals [ 16 ] and one was multi-centric [ 24 ]; all of the other ones were performed in public or university hospitals. Five were brief reports or short communications [ 16 , 35 , 36 , 47 , 49 ], six were letters to the Editor [ 11 , 15 , 37 , 42 , 46 ] or research letters [ 50 ] reporting original results, whereas the remaining 33 were full papers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Before the introduction of vaccines, the observed SARS-CoV-2 transmission was high, especially among healthcare workers worldwide [ 14 ]. This was facilitated by the fact that the symptoms of COVID-19 were highly uncharacteristic, often mild or even absent [ 15 ].…”
Section: Introductionmentioning
confidence: 99%